A fully integrated CMOS VCXO-IC with low phase noise, wide tuning range and high tuning linearity*Project supported by the National Natural Science Foundation of China (No. 61350007). (June 2015) - Yang, Yanjun; Zeng, Yun
Abstract This paper describes a low phase noise, wide tuning range and high tuning linearity CMOS voltage controlled crystal oscillator IC (VCXO-IC) with LVCMOS and LVPECL output. A differential coupled frequency doubling Colpitts oscillator is adopted to obtain low noise 2× frequency output. Wide tuning range and high linearity are simultaneously achieved by using MOS varactor arrays. The measurement results show that the designed VCXO-IC achieves −134 dBc/Hz phase noise at 1 kHz offset frequency and ± 135 ppm output frequency tuning range within 3% linearity by using 40 MHz fundamental AT-cut crystal. The VCXO-IC is fabricated in the chartered 0.35 μm standard CMOS process and occupies a total silicon area of 2.4 mm2.